The Effect of Transformational Leadership and Madrasah Climate on Elementary School Teacher Performance - Adriantoni Adriantoni; Aan Komariah; Diding Nurdin; Endang Herawan (Journal of Innovation in Educational and Cultural Research, 2023)
The purpose of this research is to find out the description of teacher performance data, transformational leadership, and school climate; and the influence of transformational leadership on teacher performance, the effect of school climate on teacher performance. The research method used is a quantitative method through an associative approach. The population in the study amounted to 94 elementary school teachers in the city of Padang. Data collection techniques through questionnaires. The results of the study revealed that: the description of the transformational leadership data of elementary school principals in the city of Padang, is included in the high category with an average of 72.14, the description of school climate is in the high category, namely 101.80, and the description of teacher performance data is also in the high category, namely 92.12; there is a positive and significant effect of transformational leadership on teacher performance of 0.917%, its contribution is 84.08%, which means that transformational leadership has a strong effect on teacher performance of 0.913%, its contribution is 83.35, which means that the school climate has a strong effect on teacher performance; there is a positive and significant effect of transformational and school climate on teacher performance of 0.604, the contribution is 36.48%, which means that transformational leadership and school climate together have a strong influence on teacher performance. The implication is that efforts to optimize teacher performance can be carried out by school principals through exemplary, motivational, democratic policies, providing rewards, making good personal relationships and approaches, and creating a sense of security and comfort at work.